Oral Language Acquisition in Preschool Children Who are Deaf and Hard-of-Hearing. (24th January 2022) - Werfel, Krystal L; Reynolds, Gabriella; Fitton, Lisa
Abstract: The purpose of this study was to compare developmental trajectories of oral language acquisition of children who are deaf and hard of hearing (DHH) and children with typical hearing across the preschool years. Thirty children who are DHH who use amplification and spoken language and 31 children with typical hearing completed an early language and literacy assessment battery every six months from age 4 to age 6. The developmental trajectories of each group's language skills were examined via growth curve analysis. Oral language skills were lower for children who are DHH than for children with typical hearing at study entry. For vocabulary, children who are DHH demonstrated growth over the two years but did not close the gap in performance over time. For morphosyntax, specifically verb tense marking, children who are DHH demonstrated growth over preschool, becoming more adult-like in their productions.